2019
DOI: 10.1002/cne.24722
|View full text |Cite
|
Sign up to set email alerts
|

DiI‐mediated analysis of presynaptic and postsynaptic structures in human postmortem brain tissue

Abstract: Most cognitive and psychiatric disorders are thought to be disorders of the synapse, yet the precise synapse defects remain unknown. Because synapses are highly specialized anatomical structures, defects in synapse formation and function can often be observed as changes in microscale neuroanatomy. Unfortunately, few methods are available for accurate analysis of synaptic structures in human postmortem tissues.Here, we present a methodological pipeline for assessing presynaptic and postsynaptic structures in hu… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
16
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(21 citation statements)
references
References 50 publications
4
16
1
Order By: Relevance
“…In accordance, the quantification technique only allowed for the identification of spines in the same x-y plane as the dendrite. Although the densities in the present study are comparable to those using similar methods [32], these combined factors likely underlie why the density of spines in the present study is lower than that identified using more sensitive methods in both rodents [81] and humans [82]. In the interpretation of the presented data, we acknowledge that these impacts may actually under-represent spine losses in the human OFC and the effect size may indeed be larger using techniques which facilitate greater resolution of spine detection.…”
Section: Discussioncontrasting
confidence: 49%
“…In accordance, the quantification technique only allowed for the identification of spines in the same x-y plane as the dendrite. Although the densities in the present study are comparable to those using similar methods [32], these combined factors likely underlie why the density of spines in the present study is lower than that identified using more sensitive methods in both rodents [81] and humans [82]. In the interpretation of the presented data, we acknowledge that these impacts may actually under-represent spine losses in the human OFC and the effect size may indeed be larger using techniques which facilitate greater resolution of spine detection.…”
Section: Discussioncontrasting
confidence: 49%
“…Synapse regulation is a central event during nervous system development and adult life. Disruptions in the establishment of synapses is associated with morphological, cognitive and psychiatric disorders, but the precise mechanisms underlying these disorders remain unknown [42]. Changes in synapse structure and function are related to paralysis and muscular atrophy in amyotrophic lateral sclerosis (ALS) [43,44], impairment of the neuromuscular junction function and therefore, motor decline [45] or social and cognitive behaviors related to autism [46].…”
Section: Discussionmentioning
confidence: 99%
“…In human neuronal disorders, the vast majority of research focuses on mature dendritic spines found in postmortem patient brain samples from adolescents and adults (Bao & Swaab, 2018; Hutsler & Zhang, 2010; Tang et al., 2014). In spite of recent techniques to minimize fixation artifacts (Das et al., 2019), postmortem brain tissue is limited to a static snapshot of synapse development. Furthermore, while rodent models capture synapse dynamics (Marrs, Green, & Dailey, 2001), most research focuses on peri‐ and postnatal periods of synaptic development.…”
Section: Introductionmentioning
confidence: 99%